Differences in primary metabolism related to quality of raspberry (Rubus idaeus L.) fruit under open field and protected soilless culture growing conditions - Fuentealba, Claudia; Álvarez, Fernanda; Ponce, Excequel; Veas, Sebastian; Salazar, Martina; Romero, Diego; Ayala-Raso, Anibal; Alvaro, Juan E.; Valdenegro, Monika; Figueroa, Carlos R.; Fuentes, Lida (Frontiers in Plant Science, 2024)
The raspberry (Rubus idaeus) fruit is characterized by good taste and high acceptability by consumers. Thus, the impact on the quality attributes and metabolites related to raspberry taste should be evaluated in crop alternatives such as the protected soilless culture. This study aimed to evaluate the metabolic changes during fruit development and postharvest of raspberry grown in open field and protected soilless culture and their relationship with quality parameters and sensory perception. In this study, the quality parameters and polar metabolites -sugar and amino acidscontent were evaluated during raspberry ripening. In addition, ripe fruit was stored at 1 ºC for five days, followed by one day of shelf life at 20 °C. The physiological and quality parameters showed typical changes during ripening in both growing conditions: a constant production of CO2, a drastic loss of firmness, an increase in weight and soluble solids content, loss of acidity, and a turning to red color from the green to fully ripe fruit stages in both growing conditions. Fruit from the protected soilless culture had significantly higher weight but a lower soluble solids content. The metabolic analysis showed differences in primary metabolites content during ripening and storage at 1 °C between both growing conditions. The raspberries grown in the open field showed higher contents of sugars such as D-glucose and D-fructose. On the contrary, the fruit from the protected soilless culture showed higher contents of some amino acids such as L-alanine, L-serine and L-valine, among others.